Implementası Metode Sosıodrama Dalam Menıngkatkan Motıvası Belajar Peserta Dıdık Dalam Pembelajaran Al Qur’an Hadıts Dı MIN 1 Sıdoarjo - Latifatul Wakhidah; Mohammad Afifulloh; , Muhammad Sulistiono (Jurnal Elementaria Edukasia, 2023)
Education is a tool that requires more attention to develop it. This is what makes a benchmark for a teacher or educator when they want to focus on presenting learning and providing the best development of learning methods in delivering the material provided. Choosing the right learning method in a lesson can create effective learning so that the learning objectives can be achieved. In this study the aim was to provide an analysis of the implementation of the learning method, namely sociodrama in learning the Qur'an Hadith in madrasas. In this research, the researcher used the Classroom Action Research (CAR) method where the researcher was directly confronted with the object under study. The application of the sociodrama method in learning the Qur'an and Hadith shows good results. Based on these results it was found that there was a significant increase in learning the Qur'an Hadith through the sociodrama method, there were only 3 students who had not completed according to the KKM.